Allenare le abilità di osservazione e descrizione nella scuola primaria in un percorso sui miscugli - Pettiti, Sara (Chimica nella Scuola, 2025)
In the following educational proposal designed for a third-grade primary school class, the topic of mixtures and the methods for their separation are addressed. A hands-on laboratory approach is adopted, granting students ample autonomy in exploring the materials available. The teacher acts as a supervisor and tutor, playing a crucial role by providing guidance. By creating an environment with appropriate stimuli, the teacher enables students to experience the joy of discovery and the progressive construction of knowledge.